Utility of FDG PET/CT in Sjögren’s Syndrome and associated lymphomas; Lymphomagenesis - Dikhra Khan; Prateek Kaushik; Sambit Sagar; Jasim Jaleel (Asia Oceania Journal of Nuclear Medicine and Biology)
Primary Sjögren syndrome (SS) is an autoimmune disease affecting exocrine glands, with predisposition to development of lymphoma (lymphomagenesis). We report a case of Sjogren’s syndrome and discuss the role of FDG PET/CT in the primary diagnosis of lymphoma transformation in SS. Furthermore, we reviewed the literature regarding the utility of FDG PET/CT to assess systemic disease activity and also its role in the SS associated lymphoma with light into the new PET tracers that can be explored for these indications in the future.  Published data suggest promising role of FDG PET/CT in SS associated lymphomas, and demands larger studies for its establishment.